Analysis of BLDC Motor Speed Error with Fuzzy Logic Control in Static and Dynamic Tests of Trimaran Boats - Pratama, Aar Mayza; Kurniawan, Edi; Gupron, Akhmad Kasan (Mataram University, 2025)
This study analyzes the speed error of Brushless DC (BLDC) motors using fuzzy logic control through static and dynamic tests on a trimaran prototype. The research method involved static validation of sensors, including photodiode, ACS758, and voltage divider, followed by dynamic tests in an artificial wave pool at set points ranging from 6000 to 10,000 RPM. The fuzzy logic controller was designed with error and change of error as input variables and PWM correction as output. The results indicate that validated sensors achieved an average error of less than 5%, ensuring reliable data for control input. In dynamic tests, fuzzy control reduced the average speed error compared to the open-loop system, with the most significant improvement observed at higher speeds. These findings demonstrate that fuzzy logic control enhances synchronization and stability of BLDC motors in marine environments, making it a promising approach for electric propulsion in multihull vessels such as trimarans.